A study on floatability of copper using modified hallimond tube - H., Aimi Noorliyana; Mohd Zaheruddin, Kasmuin; Md Fazlul, Bari; Sri Asliza, Md Amin; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.